Frontier Progress in the Establishment of Trophoblast Stem Cell and the Identification of New Cell Subtypes at the Maternal-Fetal Interface - Xiao-Bo Zhou; Chan Zhou; Yang Sun; Dong Liu; Shuang-Bo Kong; Jin-Hua Lu; Hong-Bo Qi; Hai-Bin Wang; Chun-Ying Guo; Yang Pan (Wolters Kluwer Health, 2019)
Abstract. Proper development of the human placenta is of vital importance for a successful pregnancy, and a series of pregnancy complications are considered originating from dysfunctional placentas. Like other organ system development, placentation requires large numbers of co-regulators, while the underlying molecular mechanisms orchestrating the placental formation and function are poorly understood. Although we have made many signs of progress in understanding the placental architectures and developments using mouse models, the species-specific differences impede our progress due to the lack of appropriate model systems. In the past few years, major progress has been made by the establishment of novel in-vitro self-renewing stem cell models, as well as identifying the full picture of the cellular organization of the maternal and fetal interface. Providing the tools for the investigation of placentation and reproductive-related regulation mechanism. In this review, we focus on the detailed progress of the human trophoblast stem cells culturing system, and the cellular and molecular terrain at the maternal-fetal interface, respectively, thus providing new insights into placental development.